Development of Genially-Based Interactive Learning Media for Science Education 4th Grade of Elementary School - Yolly Desnita; Abna Hidayati; Yeni Erita; Desyandri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
IPAS learning on landform topics in Grade IV elementary schools requires learning media that can transform abstract visual concepts into concrete, visual, and contextual learning experiences. Preliminary analysis showed that teachers and students had a high need for technology-based learning media, with teacher needs reaching 86% and student needs reaching 84%. This study aimed to develop, validate, examine the practicality, and evaluate the initial effectiveness of Genially-based interactive learning media integrated with Problem-Based Learning. This research employed a research and development method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The study was conducted at SDN 10 Airpura, SDN 11 Airpura, and SDN 12 Airpura. Data were collected through needs-analysis questionnaires, expert-validation sheets, teacher and student practicality questionnaires, and pre-test–post-test learning-outcome tests. The developed media integrated visual materials, instructional videos, audio, interactive navigation, group discussion activities, quizzes, and educational games. Expert validation showed that the media was highly valid, with scores of 96% for material, 98% for media design, and 91% for language, resulting in an overall validity score of 95%. Practicality testing yielded highly positive results, with teacher responses at 97% and student responses at 93%. The pre-test and post-test results increased from 55.0 to 91.1, with an N-Gain score of 0.836 (83.6%). These findings indicate that Genially-based interactive media is feasible, practical, and has strong initial effectiveness in supporting visual, contextual, and problem-oriented IPAS learning in Grade IV elementary schools.